A high temperature resistant flame retardant nanofiber membrane and its preparation method and application

By growing ultra-long hydroxyapatite nanowire layers in situ on the surface of polyurethane nanofiber membranes to form core-shell structured nanofiber membranes, the problem of easy melting and shrinkage of lithium-ion battery separators at high temperatures is solved, improving the thermal stability and electrolyte wettability of the battery, and enhancing the safety and electrochemical performance of the battery.

CN118814364BActive Publication Date: 2025-01-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411305018.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-14
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

Existing lithium-ion battery separators are prone to melting and shrinkage at high temperatures, leading to battery short circuits. Furthermore, the low porosity and low wettability of polyolefin separators affect battery performance and safety.

Method used

Polyurethane nanofiber membranes were prepared by electrospinning, and ultra-long hydroxyapatite nanowire layers were grown in situ on their surface to form a core-shell structured high-temperature resistant and flame-retardant nanofiber membrane, which improved thermal stability and electrolyte wettability.

Benefits of technology

It significantly improves the safety and electrochemical performance of lithium-ion batteries, inhibits dendrite growth, enhances the thermal stability and electrolyte wettability of batteries, and possesses excellent flame retardant properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118814364B_ABST
    Figure CN118814364B_ABST
Patent Text Reader

Abstract

A high temperature resistant flame retardant nanofiber membrane and its preparation method and application belong to the technical field of lithium ion battery materials. The high temperature resistant flame retardant nanofiber membrane is a polyurethane-based nanofiber membrane with an ultra-long hydroxyapatite nanowire layer coaxially coated on the surface of polyurethane nanofibers. The preparation method is: polyurethane is dissolved in an organic solvent to prepare a spinning solution, and the spinning solution is used to prepare a polyurethane nanofiber membrane by an electrospinning method. Ultra-long hydroxyapatite nanowires are in situ grown on the surface of polyurethane nanofibers by a calcium oleate precursor solvothermal method. The ultra-long hydroxyapatite nanowire layer on the surface of the high temperature resistant flame retardant nanofiber membrane prepared by the present invention has high thermal dimensional stability, and the ultra-long hydroxyapatite nanowires have the ability to regulate lithium ion transmission and induce uniform lithium deposition, thereby inhibiting dendrite growth and reducing the overpotential during the charge and discharge cycle. At the same time, it has extremely high flame retardant properties, which significantly improves the electrochemical performance and safety of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of lithium-ion batteries, and specifically relates to a high-temperature resistant and flame-retardant nanofiber membrane and a preparation method and application thereof. Background Art

[0002] In recent years, due to the increasing consumption of fossil energy, there is an urgent need for clean energy to replace fossil energy. At the same time, clean, stable and efficient energy storage systems have also attracted widespread attention. Lithium-ion batteries (LIBs) with high energy density and stable cycle performance have rapidly dominated the energy storage system market for portable electronic devices such as smartphones, laptops and cameras. However, improper use of lithium batteries in life can easily cause safety problems such as combustion and explosion. As an important component of lithium-ion batteries, diaphragms have a significant impact on the capacity and performance of batteries. Using diaphragms to optimize battery performance, extend battery life, and solve battery safety issues is an effective method.

[0003] At present, most of the lithium-ion battery separators on the market focus on polyolefin separators such as polyethylene (PE) and polypropylene (PP). These polyolefin microporous membranes have good chemical stability and high mechanical strength. However, the low porosity and poor wettability of polyolefin membranes with polar liquid electrolytes seriously affect the battery resistance, energy density and rate capability of LIB. Polyolefin materials will melt and shrink at high temperatures, causing battery short circuits. The release of a large amount of heat in a short period of time causes the lithium-ion battery to burn or even explode. The ideal separator should have low interfacial resistance, high electrolyte wettability and uniform pore distribution to meet the requirements of normal operation of the battery in different applications. The separator needs to have the characteristics of high thermal stability, high mechanical strength and high wettability to meet these requirements. Therefore, it is very important to develop high thermal stability, high mechanical strength and high wettability separators to replace traditional commercial separators to further improve the performance and safety of lithium-ion batteries.

[0004] The electrospinning process has received extensive attention in the past two decades. Electrospinning technology can continuously produce micron-scale nanofiber membranes. Nanofiber membranes have large specific surface area, high porosity, small pore size, and strong adsorption, which can improve the wettability and thermal stability of the membrane. With the development and commercial production of large-scale electrospinning equipment, mass production of nanofibers has also become possible. For example, patent CN105428572A prepares lithium-ion battery separators through electrospinning, which have high temperature resistance, high porosity and flexibility, but this separator does not have flame retardancy. Summary of the invention

[0005] In view of the deficiencies in the prior art, one of the objectives of the present invention is to provide a nanofiber membrane having good high temperature resistance, flame retardancy, high wettability, thin thickness and low electrical resistance.

[0006] The second object of the present invention is to provide a method for preparing a high temperature resistant and flame retardant nanofiber membrane, which is easy to control and can produce a high-quality diaphragm material that reduces battery quality risks and effectively improves battery safety.

[0007] The third object of the present invention is to provide application of the nanofiber membrane in lithium-ion batteries.

[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0009] A high temperature resistant and flame retardant nanofiber membrane, which is a polyurethane-based nanofiber membrane with an ultra-long hydroxyapatite nanowire layer coaxially coated on the surface of polyurethane nanofibers.

[0010] The high temperature resistant flame retardant nanofiber membrane is a core-shell structure, wherein the polyurethane nanofiber obtained by electrospinning serves as a core layer; and the super long hydroxyapatite nanowires radially arranged on the surface of the polyurethane nanofiber constitute a hydroxyapatite nanowire layer as a shell layer.

[0011] Preferably, the diameter of the polyurethane nanofiber is 200nm~600nm, the diameter of the ultra-long hydroxyapatite nanowire is 50nm~200nm, and the length is 3µm~10µm.

[0012] Preferably, the thickness of the polyurethane-based nanofiber membrane is 10µm to 100µm, particularly preferably 15µm to 45µm.

[0013] The high temperature resistant flame retardant nanofiber membrane of the present invention is provided with a core layer of polyurethane nanofibers obtained by electrospinning and a shell layer of ultra-long hydroxyapatite nanowires in situ modified on the surface of the core layer. The polyurethane material has excellent thermal stability, and the heat resistance of the polyurethane-based nanofiber membrane can be significantly improved by using this material as a matrix. In addition, the carbonyl group in the polyurethane molecular structure has a higher compatibility with the electrolyte, so that the polyurethane-based nanofiber membrane has an extremely high liquid absorption rate, thereby enhancing the ionic conductivity of the polyurethane-based nanofiber membrane. The core layer is prepared by an electrospinning process to form a porous structure, which further significantly improves the wettability and liquid retention rate of the electrolyte. The ultra-long hydroxyapatite nanowires also have high thermal dimensional stability, and the ultra-long hydroxyapatite nanowires also have the ability to regulate lithium ion transmission and induce uniform lithium deposition, thereby inhibiting dendrite growth and reducing the overpotential during the charge and discharge cycle. At the same time, it has extremely high flame retardant properties, significantly improving the electrochemical performance and safety of the battery.

[0014] The present application also provides a method for preparing a high temperature resistant flame retardant nanofiber membrane, the preparation method comprising the following steps:

[0015] (1) Preparation of polyurethane nanofiber membrane: Polyurethane is dissolved in an organic solvent to prepare a spinning solution, and the spinning solution is used to prepare the polyurethane nanofiber membrane by an electrospinning method.

[0016] Furthermore, the specific process of electrospinning is: adding the spinning solution into the syringe, electrospinning is performed under the conditions of voltage of 15kV~30kV, extrusion speed of 1.5ml / h~3ml / h, and receiving distance of 8cm~25cm. The polyurethane nanofibers are collected and hot-pressed at 80℃~120℃ and 5MPa~15MPa for 3min~15min to obtain the polyurethane nanofiber membrane.

[0017] (2) Preparation of ultra-long hydroxyapatite nanowire layer: Ultra-long hydroxyapatite nanowires were in situ grown on the surface of polyurethane nanofibers using a calcium oleate precursor solvothermal method.

[0018] Furthermore, the specific process of step (2) is: adding calcium chloride aqueous solution, sodium hydroxide aqueous solution and sodium dihydrogen phosphate aqueous solution to the mixture of oleic acid and ethanol respectively, and mechanically stirring to obtain a reaction solution. The polyurethane nanofiber membrane obtained in step (1) is placed in the reaction solution to perform a heat treatment reaction. After the heat treatment reaction is completed, the membrane is washed and vacuum dried to obtain the final high temperature resistant flame retardant nanofiber membrane.

[0019] Preferably, in step (1), the organic solvent is one or a mixture of two or more of dimethylacetamide DMAC, dimethylformamide DMF, and dimethyl sulfoxide DMSO, and the solid content of the spinning solution is 5% to 30%.

[0020] Preferably, in step (2), the concentrations of the calcium chloride aqueous solution, sodium hydroxide aqueous solution, and sodium dihydrogen phosphate aqueous solution are 0.05 mol / L-0.2 mol / L, 0.5 mol / L-2 mol / L, and 0.1 mol / L-3 mol / L, respectively; and the mass ratio of the reactants is calcium chloride aqueous solution: sodium hydroxide aqueous solution: sodium dihydrogen phosphate aqueous solution: oleic acid: ethanol = (15-20): (10-30): (5-15): (5-18): (10-35).

[0021] Preferably, in step (2), the heat treatment reaction conditions are: heat treatment at 150°C to 220°C for 12h to 48h.

[0022] Preferably, in step (2), the heat treatment reaction is carried out in a stainless steel reactor.

[0023] Preferably, in step (2), the solvent used for washing is ethanol.

[0024] The present invention avoids using a polyolefin porous membrane and uses a composite diaphragm formed by combining polyurethane with high thermal stability and ultra-long hydroxyapatite nanowire materials, which can fully improve the thermal shrinkage performance of the diaphragm.

[0025] The third purpose of the present application is to provide an application of a high temperature resistant and flame retardant nanofiber membrane, which is applied to lithium ion batteries. The prepared high temperature resistant and flame retardant nanofiber membrane has excellent performance in lithium ion batteries.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The high temperature resistant flame retardant nanofiber membrane of the present invention innovatively sets a coaxially coated ultra-long hydroxyapatite nanowire layer, including a core layer of polyurethane nanofibers obtained by electrospinning and a shell layer of ultra-long hydroxyapatite nanowires in situ modified on its surface. The core layer and the shell layer can synergistically enhance the heat resistance of the separator and significantly improve the safety performance of the battery.

[0028] 2. The high temperature resistant flame retardant nanofiber membrane of the present invention has excellent electrolyte wettability and liquid retention rate. The carbonyl group in the polyurethane molecular structure has a higher compatibility with the electrolyte, so that the high temperature resistant flame retardant nanofiber membrane has a very high liquid absorption rate, thereby enhancing the ionic conductivity of the high temperature resistant flame retardant nanofiber membrane. In addition, the core layer is prepared by an electrospinning process to form a porous structure, which further significantly improves the electrolyte wettability and liquid retention rate. At the same time, the large specific surface area of ​​the ultra-long hydroxyapatite nanowires also improves the electrolyte wettability.

[0029] 3. The high temperature resistant flame retardant nanofiber membrane of the present invention has the ability to regulate lithium ion transmission and induce uniform lithium deposition. The ultra-long hydroxyapatite nanowires have the ability to regulate lithium ion transmission and induce uniform lithium deposition, thereby inhibiting dendrite growth, reducing the overpotential during the charge and discharge cycle, and improving the electrochemical performance of the battery.

[0030] 4. The high temperature resistant flame retardant nanofiber membrane of the present invention has flame retardant function. The ultra-long hydroxyapatite nanowire has excellent flame retardant performance. Coating it on the surface of polyurethane nanofiber can significantly improve the flame retardant performance of the high temperature resistant flame retardant nanofiber membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is the electrolyte wettability of the separator in Examples 1 to 3 of the present invention and Comparative Examples 1 to 2.

[0032] Figure 2 It is a battery performance diagram of the separators in Examples 1 to 3 of the present invention and Comparative Examples 1 to 2. DETAILED DESCRIPTION

[0033] The present application is described in detail below in conjunction with embodiments, but the present application is not limited to the following embodiments.

[0034] Example 1: Preparation of high temperature resistant flame retardant nanofiber membrane, comprising the following steps:

[0035] 1) Preparation of polyurethane nanofiber membrane: 2g polyurethane was dissolved in 8g organic solvent DMAC to prepare spinning solution. The spinning solution was added to the syringe and electrospun at a voltage of 18kV, an extrusion speed of 1.5ml / h, and a receiving distance of 15cm. The polyurethane nanofibers were collected and hot-pressed at 100℃ and 8MPa for 3min to obtain the polyurethane nanofiber membrane;

[0036] 2) Preparation of ultra-long hydroxyapatite nanowire layer: 0.1 mol / L calcium chloride aqueous solution, 0.8 mol / L sodium hydroxide aqueous solution, and 1 mol / L sodium dihydrogen phosphate aqueous solution were added to the mixture of oleic acid and ethanol, respectively, and mechanically stirred. The mass ratio of the reactants is calcium chloride aqueous solution: sodium hydroxide aqueous solution: sodium dihydrogen phosphate aqueous solution: oleic acid: ethanol = 15:20:12:10:20. The reaction solution was then transferred to a stainless steel reactor, and the polyurethane nanofiber membrane obtained in step (1) was placed in the reaction solution and heat treated at 180°C for 24 hours. Reaction. After the reaction is completed, it is washed with ethanol and vacuum dried to obtain the final high temperature resistant flame retardant nanofiber membrane.

[0037] In this embodiment, the diameter of the polyurethane nanofiber is 200 nm, the diameter of the ultra-long hydroxyapatite nanowire is 50 nm, and the length is 5 μm. The thickness of the high temperature resistant flame retardant nanofiber membrane is 15 μm.

[0038] Example 2: Preparation of high temperature resistant flame retardant nanofiber membrane, comprising the following steps:

[0039] 1) Preparation of polyurethane nanofiber membrane: 3g polyurethane was dissolved in 7g organic solvent DMF to prepare spinning solution. The spinning solution was added to the syringe and electrospun at a voltage of 15kV, an extrusion speed of 2ml / h, and a receiving distance of 25cm. The polyurethane nanofibers were collected and hot-pressed at 80℃ and 15MPa for 15min to obtain the polyurethane nanofiber membrane;

[0040] 2) Preparation of ultra-long hydroxyapatite nanowire layer: 0.2 mol / L calcium chloride aqueous solution, 0.5 mol / L sodium hydroxide aqueous solution, and 3 mol / L sodium dihydrogen phosphate aqueous solution were added to the mixture of oleic acid and ethanol, respectively, and mechanically stirred. The mass ratio of the reactants is calcium chloride aqueous solution: sodium hydroxide aqueous solution: sodium dihydrogen phosphate aqueous solution: oleic acid: ethanol = 20:30:15:18:10. The reaction solution was then transferred to a stainless steel reactor, and the polyurethane nanofiber membrane obtained in step (1) was placed in the reaction solution and heat treated at 150°C for 48 hours. Reaction. After the reaction is completed, it is washed with ethanol and vacuum dried to obtain the final high temperature resistant flame retardant nanofiber membrane.

[0041] In this embodiment, the diameter of the polyurethane nanofiber is 600 nm, the diameter of the ultra-long hydroxyapatite nanowire is 100 nm, and the length is 10 μm. The thickness of the high temperature resistant flame retardant nanofiber membrane is 45 μm.

[0042] Example 3: Preparation of high temperature resistant flame retardant nanofiber membrane, comprising the following steps:

[0043] 1) Preparation of polyurethane nanofiber membrane: 0.5g polyurethane was dissolved in 9.5g organic solvent DMSO to prepare spinning solution. The spinning solution was added to the syringe and electrospun at a voltage of 30kV, an extrusion speed of 3ml / h, and a receiving distance of 8cm. The polyurethane nanofibers were collected and hot-pressed at 120℃ and 5MPa for 10min to obtain the polyurethane nanofiber membrane;

[0044] 2) Preparation of ultra-long hydroxyapatite nanowire layer: 0.05 mol / L calcium chloride aqueous solution, 2 mol / L sodium hydroxide aqueous solution, and 0.1 mol / L sodium dihydrogen phosphate aqueous solution were added to the mixture of oleic acid and ethanol, respectively, and mechanically stirred. The mass ratio of the reactants is calcium chloride aqueous solution: sodium hydroxide aqueous solution: sodium dihydrogen phosphate aqueous solution: oleic acid: ethanol = 18:10:5:5:35. The reaction solution was then transferred to a stainless steel reactor, and the polyurethane nanofiber membrane obtained in step (1) was placed in the reaction solution and heat treated at 220°C for 12 hours. Reaction. After the reaction is completed, it is washed with ethanol and vacuum dried to obtain the final high temperature resistant flame retardant nanofiber membrane.

[0045] In this embodiment, the diameter of the polyurethane nanofiber is 500 nm, the diameter of the ultra-long hydroxyapatite nanowire is 200 nm, and the length is 3 μm. The thickness of the high temperature resistant flame retardant nanofiber membrane is 100 μm.

[0046] Comparative Example 1: Comparative Example 1 is a commercial ceramic coated diaphragm with a thickness of 12 μm.

[0047] Comparative Example 2: Comparative Example 2 is a commercial PE base film with a thickness of 12 μm.

[0048] Comparative Example 3: Comparative Example 3 is a polyurethane nanofiber membrane, comprising the following steps:

[0049] 2g polyurethane was dissolved in 8g organic solvent DMAC to prepare spinning solution. The spinning solution was added into the syringe and electrospun at voltage 18kV, extrusion speed 1.5ml / h, and receiving distance 15cm. The solution was collected and hot pressed at 100℃ and 8MPa for 3min to obtain polyurethane nanofiber membrane.

[0050] In this comparative example, the diameter of the polyurethane nanofiber is 200 nm, the diameter of the ultra-long hydroxyapatite nanowire is 50 nm, and the length is 5 µm.

[0051] Performance Test 1: The diaphragms obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were tested for thermal shrinkage and electrolyte wettability. The specific test methods are as follows. The test results are shown in Tables 1 and Figure 1 .

[0052] Thermal shrinkage rate: Cut the diaphragm into 100mm×100mm film samples, measure their longitudinal and transverse lengths, put them into a vacuum oven and bake them for 1h respectively, take out the diaphragm samples, cool them to room temperature, measure their longitudinal and transverse lengths again, calculate the thermal shrinkage rate, and characterize the heat resistance of the diaphragm. Test them at three temperatures of 105℃, 120℃ and 150℃ respectively.

[0053] Electrolyte Wettability: The electrolyte wettability uses electrolyte solvent (ethylene carbonate and dimethyl carbonate, with a mass ratio of 1:1) as the test object to observe the diffusion of the electrolyte at different times.

[0054] The separators in the examples and comparative examples were assembled into soft-pack batteries, and the rate curves were tested. The results are as follows: Figure 2 shown.

[0055] Table 1

[0056]

[0057] As shown in Table 1, the heat resistance of the diaphragms provided by Examples 1 to 3 is much higher than that of Comparative Examples 1 to 2, indicating that the high temperature resistant flame retardant nanofiber membrane significantly improves the thermal stability of the diaphragm. Figure 1 It can be seen that the electrolyte wettability of the diaphragms provided in Examples 1 to 3 is significantly improved compared with the ceramic coated diaphragm provided in Comparative Example 1 and the commercial PE base film provided in Comparative Example 2, indicating that the spinning layer structure and composition can significantly improve the electrolyte wettability of the diaphragm. Figure 1 Analysis shows that the high temperature resistant and flame retardant nanofiber membrane provided by the present invention has high electrolyte wettability and thermal stability of the diaphragm.

[0058] Depend on Figure 2 It can be seen that the ceramic coated diaphragm in Comparative Example 1 has no significant change in rate performance compared to the traditional PE-based membrane in Comparative Example 2. The rate performance of the nanofiber membrane in Examples 1 to 3 is significantly improved. This is because the carbonyl group in the polyurethane molecular structure has a higher compatibility with the electrolyte, which makes the diaphragm have an extremely high liquid absorption rate. In addition, the nanofiber core layer is prepared by an electrospinning process to form a porous structure, which further significantly improves the wettability and liquid retention rate of the electrolyte. At the same time, the large specific surface area of ​​the ultra-long hydroxyapatite nanowires also improves the electrolyte wettability.

[0059] The flame retardancy of the diaphragm was verified by a combustion experiment. The specific operation is as follows: the diaphragm is cut into a 100mm×20mm film sample, the diaphragm is burned with an open flame, and the burning state of the diaphragm is observed after 20s. After the combustion experiment, it was found that the diaphragms in Examples 1 to 3 shrank by about 10mm, with no obvious signs of burning; the diaphragm in Comparative Example 3 was almost completely burned, with only a small amount of about 2mm left. This shows that compared with Comparative Example 3, the diaphragms in Examples 1 to 3 have better flame retardant properties. This is because the ultra-long hydroxyapatite nanowires have excellent flame retardant properties. Coating it on the surface of polyurethane nanofibers can significantly improve the flame retardant properties of high temperature resistant flame retardant nanofiber membranes.

[0060] The above are only some of the embodiments of the invention, and do not constitute any formal limitation on the present application. All raw material ratios, upper and lower limits of working conditions and interval values ​​in the preparation process of the present application can realize the present application, and the embodiments are not listed one by one here. Any person familiar with this profession, without departing from the technical solution of the present application, can make some changes or modifications to the equivalent embodiments of the decoration by using the above technical content. However, any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present application without departing from the content of the technical solution of the present application are still within the scope of the technical solution of the present application.

Claims

1. A method for preparing a high temperature resistant flame retardant nanofiber membrane, characterized in that: The preparation method comprises the following steps: (1) Preparation of polyurethane nanofiber membrane: polyurethane is dissolved in an organic solvent to prepare a spinning solution, and the spinning solution is used to prepare a polyurethane nanofiber membrane by an electrospinning method; (2) Preparation of ultra-long hydroxyapatite nanowire layer: ultra-long hydroxyapatite nanowires are grown in situ on the surface of polyurethane nanofibers by using a calcium oleate precursor solvent thermal method; the calcium oleate precursor solvent is prepared by adding a calcium chloride aqueous solution, a sodium hydroxide aqueous solution, and a sodium dihydrogen phosphate aqueous solution to a mixture of oleic acid and ethanol, respectively, and mechanically stirring to obtain a calcium oleate precursor solvent; The specific process of electrospinning is: add the spinning solution into the syringe, perform electrospinning under the conditions of voltage of 15kV~30kV, extrusion speed of 1.5ml / h~3ml / h, and receiving distance of 8cm~25cm; collect the polyurethane nanofibers, and heat press them for 3min~15min at 80℃~120℃ and 5MPa~15MPa to obtain the polyurethane nanofiber membrane; The polyurethane nanofiber membrane obtained in step (1) is placed in a calcium oleate precursor solvent to perform a heat treatment reaction; after the heat treatment reaction is completed, the membrane is washed and vacuum dried to obtain a final high temperature resistant flame retardant nanofiber membrane; High temperature resistant and flame retardant nanofiber membranes are used in lithium-ion batteries.

2. The method for preparing a high temperature resistant flame retardant nanofiber membrane according to claim 1, characterized in that: In the step (1), the organic solvent is one or a mixture of two or more of dimethylacetamide DMAC, dimethylformamide DMF, and dimethyl sulfoxide DMSO, and the solid content of the spinning solution is 5% to 30%.

3. The method for preparing a high temperature resistant flame retardant nanofiber membrane according to claim 1, characterized in that: In the step (2), the concentrations of the calcium chloride aqueous solution, the sodium hydroxide aqueous solution, and the sodium dihydrogen phosphate aqueous solution are 0.05 mol / L-0.2 mol / L, 0.5 mol / L-2 mol / L, and 0.1 mol / L-3 mol / L, respectively; the mass ratio of the reactants is calcium chloride aqueous solution: sodium hydroxide aqueous solution: sodium dihydrogen phosphate aqueous solution: oleic acid: ethanol = (15-20): (10-30): (5-15): (5-18): (10-35); the heat treatment reaction conditions are: heat treatment at 150°C-220°C for 12h-48h; the heat treatment reaction is carried out in a stainless steel reactor; and the solvent used for cleaning is ethanol.

4. A high temperature resistant flame retardant nanofiber membrane prepared by the method for preparing a high temperature resistant flame retardant nanofiber membrane according to any one of claims 1 to 3, characterized in that: The high temperature resistant and flame retardant nanofiber membrane is a polyurethane-based nanofiber membrane with an ultra-long hydroxyapatite nanowire layer coaxially coated on the surface of polyurethane nanofibers.

5. The high temperature resistant and flame retardant nanofiber membrane according to claim 4, characterized in that: The high temperature resistant flame retardant nanofiber membrane is a core-shell structure, wherein the polyurethane nanofiber obtained by electrospinning serves as a core layer; and the super long hydroxyapatite nanowires radially arranged on the surface of the polyurethane nanofiber constitute a hydroxyapatite nanowire layer as a shell layer.

6. The high temperature resistant and flame retardant nanofiber membrane according to claim 4, characterized in that: The diameter of the polyurethane nanofiber is 200nm~600nm, the diameter of the ultra-long hydroxyapatite nanowire is 50nm~200nm, and the length is 3µm~10µm; the thickness of the polyurethane-based nanofiber membrane is 10µm~100µm.

Citation Information

Patent Citations

  • Preparation method of electrospun composite membrane for lithium ion battery

    CN105428572A

  • Polylactic acid composite film and preparation method thereof

    CN116641228A